Faktor Determinan Pemberian ASI Ekslusif Di Puskesmas Andongsari - Yulianing Tyas P.S; Gumiarti Gumiarti; Syiska Atik M (Jurnal Rumpun Ilmu Kesehatan, 2023)
Exclusive breastfeeding is giving breast milk without other additional food and drinks to babies aged 0-6 months. Coverage of babies receiving exclusive breast milk in 2021 in Indonesia is 56.9%. At the Andongsari Jember Community Health Center in 2021 the coverage of exclusive breastfeeding was 9.2%. This coverage has decreased compared to 2020, amounting to 48.9%. The aim of this research is to determine the determinant factors for exclusive breastfeeding at the Andongsari Community Health Center. The research design used is descriptive. The population used by mothers breastfeeding babies aged 6-24 months was 100 people, the sample was 80 people. The technique used was simple random sampling with a questionnaire measuring instrument. The research results showed that knowledge was good 83.8%, fair 11.2%, less 5%, favorable attitude 55% unfavorable 45%, positive perception 50%, negative 50%, family income below UMK 82.5%, above UMK 17.5%, moderate husband support 68.8% high 31.2%, and the role of health workers supports 68.8%, does not support 31.2%. Almost all mothers have good knowledge about exclusive breastfeeding, most have a favorable attitude, half have positive perceptions, almost all have family incomes below the UMK, most have moderate husband support and most of the health workers' roles are supportive. It is recommended that breastfeeding mothers be able to increase and apply their knowledge in exclusive breastfeeding.